2013
DOI: 10.1002/er.3111
|View full text |Cite
|
Sign up to set email alerts
|

Energy harvesting system using reverse electrodialysis with nanoporous polycarbonate track-etch membranes

Abstract: SUMMARY Energy harvesting technology has recently gained attraction as it enables the utilization of diverse ambient energy sources. Reverse electrodialysis (RED) is such a technique that converts electrical energy from the concentration gradient between a concentrated solution (e.g., seawater) and a diluted solution (e.g., fresh water). We experimentally investigated a RED device using nanoporous polycarbonate track‐etch membranes. We performed the parametric study by varying the concentration differences, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 52 publications
(57 reference statements)
2
49
0
Order By: Relevance
“…[7] Harvesting clean energy from the ambient environment is an environmentally and economically feasible way, compared with the fossil-based energy resources. To date, the osmotic energy conversion process has been extensively studied with polymeric [11][12][13] and inorganic materials, [14][15][16] showing superior performance due to excellent selectivity and high ionic flux. [8] Recently, inspired by the exceptional ion transport properties, ion-channelmimetic nanofluidic systems in solid-state materials become an intriguing research area in energy conversion and storage.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Harvesting clean energy from the ambient environment is an environmentally and economically feasible way, compared with the fossil-based energy resources. To date, the osmotic energy conversion process has been extensively studied with polymeric [11][12][13] and inorganic materials, [14][15][16] showing superior performance due to excellent selectivity and high ionic flux. [8] Recently, inspired by the exceptional ion transport properties, ion-channelmimetic nanofluidic systems in solid-state materials become an intriguing research area in energy conversion and storage.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the previously reported membrane system, our membrane with asymmetrical structures exhibited higher power density (Table S4). With regard to the relatively low pore density of the PET membrane (10 8 cm −2 ), the power density values can be further increased by using ion‐track‐etched pores with higher pore density (10 9−10 cm −2 ).…”
Section: Resultsmentioning
confidence: 63%
“…The variation in the concentration differences considerably affects the electrochemical performance of the RED [16,24]. We characterize our RED system for the change in the concentrations of both the concentrated and the diluted solutions.…”
Section: Resultsmentioning
confidence: 99%
“…They showed that the membrane resistance can decrease with increasing the water uptake. An extensive analysis is yet to be performed for the major parameters of the NH 4 HCO 3 -RED system, compared with various conventional NaCl-RED system study [22][23][24][25][26][27]. The power reported in the previous studies is somewhat insufficient for practical applications [19,20].…”
Section: Introductionmentioning
confidence: 93%